2005
DOI: 10.1002/art.21385
|View full text |Cite
|
Sign up to set email alerts
|

Refining the complex rheumatoid arthritis phenotype based on specificity of the HLA–DRB1 shared epitope for antibodies to citrullinated proteins

Abstract: Objective. The main genetic risk factor for rheumatoid arthritis (RA), the HLA region, has been known for 25 years. Previous research has demonstrated, within the RA population, an association between HLA-DRB1 alleles carrying the shared epitope (SE) and antibodies directed against cyclic citrullinated peptides (anti-CCP antibodies). We undertook this study to make the first comparison of SE allele frequencies in the healthy population with those in RA patients who do or do not harbor anti-CCP antibodies.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
393
1
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 507 publications
(438 citation statements)
references
References 17 publications
35
393
1
9
Order By: Relevance
“…40,47 Thus, it is not surprising that linkage evidence at the MHC is strongly influenced by the presence of these autoantibodies. 39 Interestingly, our data provide some evidence that other regions, particularly on chromosomes 4, 5 and 7, may also carry susceptibility alleles that are more closely linked to anti-CCP þ disease. In contrast, neither sex nor HLA status significantly influenced linkage results outside of the MHC.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…40,47 Thus, it is not surprising that linkage evidence at the MHC is strongly influenced by the presence of these autoantibodies. 39 Interestingly, our data provide some evidence that other regions, particularly on chromosomes 4, 5 and 7, may also carry susceptibility alleles that are more closely linked to anti-CCP þ disease. In contrast, neither sex nor HLA status significantly influenced linkage results outside of the MHC.…”
Section: Discussionmentioning
confidence: 63%
“…38 There is a strong association with the presence of anti-CCP antibodies and the HLA 'SE' alleles that are classically associated with RA. 39,40 Furthermore, anti-CCP antibodies are predictive of progressive erosive disease. 41 Thus, these antibodies may mark a genetically more homogeneous subset of RA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it was initially thought that HLA did not play a role in the etiology of anti‐CCP–negative RA 12, several studies have now shown its association with seronegative disease 5, 8, 13, 14. More recently, this association has been pinpointed to 2 amino acid positions within HLA molecules: position 11 of HLA–DRB1 and position 9 of HLA–B 15.…”
mentioning
confidence: 99%